The utilization of digital technology in music education at Universitas Negeri Yogyakarta - Drijastuti Jogjaningrum (Imaji, 2022)
As is known, the most Indonesians have used digital technology in their daily lives, including in representing the art of music. As one of the adaptive educational institutions, Universitas Negeri Yogyakarta (UNY) is deemed necessary to further enhance the essence of music education that is integrated with digital technology. Based on the results of the literature studies and best practices regarding music technology and art, with a qualitative method that produces descriptive data, it can be seen that the foundation of today's music technology is to represent sound into a series of digital data. The fundamental shift of sound representation to digital media, has challenged the orientation of digital technology and its various effects on the process of music creation, presentation and publication. In this paper, the author examines three main functions of using digital technology in the context of music, namely music technology as a tool, instrument and collaboration media. The results of this study are suggestions for an integrated approach between music and digital technology in the educational process for music arts students. Keywords: Music, Technology, Integration